Computer-assisted HIV prevention for youth with substance use disorders. - Marsch, Lisa A; Grabinski, Michael J; Bickel, Warren K; Desrosiers, Alethea; Guarino, Honoria; Muehlbach, Britta; Solhkhah, Ramon; Taufique, Shilpa; Acosta, Michelle (Substance use & misuse, 2011)
We developed an interactive, customizable, Web-based program focused on the prevention of HIV, sexually transmitted infections, and hepatitis among youth. Results from a randomized, controlled trial with youth in treatment for substance use demonstrated that this Web-based tool, when provided as an adjunct to an educator-delivered prevention intervention, increased accurate prevention knowledge, increased intentions to carefully choose partners, and was perceived as significantly more useful relative to the educator-delivered intervention when provided alone. Results suggest this Web-based program may be effective and engaging and may increase the adoption of effective HIV and disease prevention science for youth. Limitations are discussed.
Keywords: Adolescent; Adolescent Behavior; Analysis of Variance; Child; Computers; Condoms; Counseling; Curriculum; Female; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Internet; Male; New York City; Sexually Transmitted Diseases; Substance Abuse Treatment Centers; Substance-Related Disorders; User-Computer Interface